Influence of ict on the shaping of creativity and cooperation skills of children and teenagers – differences between students’ and teachers’ opinions (research report) - Eunika Baron-Polańczyk (Lubelski Rocznik Pedagogiczny, 2021)
Introduction: The article presents a fragment of diagnostic-correlative research of a mixed character, identifying pupils’ information literacy in the use of ICT methods and tools. Together, 2510 pupils and 1110 teachers were involved. Research Aim: The author aim to answer the question defining the effects of using ICT by children and teenagers (the level of significance of the impact of new media) in the area of shaping creativity and cooperation skills. Research Method: The method of diagnostic survey (questionnaire and interview) and statistical methods (chi-square test of independence and Pearson's correlation coefficient) were used. Results: It was established that: 1) according to the aggregate hierarchy of importance of ICT interactions, the development of creativity and cooperation was given a great deal of importance by students (second place), and a high importance (third place) by teachers; 2) there is a relationship (correlation: weak negative – r = -0.03) between the students 'opinion and teachers' perceptions as to the effects of using ICT by children and adolescents, manifested by the development of creative attitudes and group work skills; 3) calculations of differentiating factors showed significant statistical differences between the effects of ICT impacts on children and adolescents in terms of the development of creativity and collaboration and the stage of pupils' education. Conclusions: There is a noticeable discrepancy between the opinions of students and teachers, the disturbing “separation” of the world of children and youth (“Us”) from the world of teachers (“Them”).